2009
DOI: 10.5009/gnl.2009.3.4.338
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Obstructive Jaundice Caused by Paradoxical Reaction during Antituberculous Chemotherapy for Abdominal Tuberculosis

Abstract: Abdominal tuberculosis is not a rare disease, but obstructive jaundice caused by tuberculosis (tuberculous lymphadenitis, tuberculous enlargement of the head of pancreas, and/or tuberculous stricture of the biliary tree) is rare. We recently experienced a case of obstructive jaundice as a result of paradoxical reaction of periportal tuberculous lymphadenopathy that was treated successfully with corticosteroid and biliary drainage. No similar cases have been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In the past decade, there have been several case reports demonstrating that biliary obstruction can be treated without surgery, based on the preoperative biopsy results (19,22,23,34,35). EUS-FNAB is known to be quite useful in the diagnosis of pancreatic lesions (36).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there have been several case reports demonstrating that biliary obstruction can be treated without surgery, based on the preoperative biopsy results (19,22,23,34,35). EUS-FNAB is known to be quite useful in the diagnosis of pancreatic lesions (36).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical reactions are seen in up to 25% of patients1 with tuberculosis after the initiation of antitubercular therapy, and are characterised by clinical deterioration or radiological worsening of pre-existing tuberculosis, or the development of new lesions 2. Typically these reactions occur following an initial phase of response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…60 Few cases with paradoxical response with worsening of liver function tests needing biliary drainage have been reported. 1,61 Therefore, the total duration of therapy may be decided on basis of resolution of imaging findings in these patients. Some reports have indicated that patients respond as well with 6 months of ATT, but the mode of follow-up was not mentioned in the report.…”
Section: Treatment Of Pancreatic Tuberculosismentioning
confidence: 99%